2018
DOI: 10.1016/j.envint.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal lead, cadmium and mercury exposure and associations with motor skills at age 7 years in a UK observational birth cohort

Abstract: BackgroundLead and mercury are freely transferred across the placenta, while cadmium tends to accumulate in the placenta. Each contributes to adverse neurological outcomes for the child. Although prenatal heavy metal exposure has been linked with an array of neurodevelopmental outcomes in childhood, its association with the development of motor skills in children has not been robustly studied.Aims/objectiveThe aim of the present study was to investigate the association between prenatal exposure to lead, cadmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The association with lead was found only for the newborn boys. Interestingly, a recent study suggested that male fetuses are particularly susceptible to maternal exposure effects on newborn TL [14], and males appear more susceptible to neurotoxicity in relation to prenatal lead exposure [50, 51]. An inverse association between blood lead and telomere length has been previously reported for 8-year-old children ( n = 99) with low-to-moderate exposure to lead from industrial emission [27].…”
Section: Discussionmentioning
confidence: 99%
“…The association with lead was found only for the newborn boys. Interestingly, a recent study suggested that male fetuses are particularly susceptible to maternal exposure effects on newborn TL [14], and males appear more susceptible to neurotoxicity in relation to prenatal lead exposure [50, 51]. An inverse association between blood lead and telomere length has been previously reported for 8-year-old children ( n = 99) with low-to-moderate exposure to lead from industrial emission [27].…”
Section: Discussionmentioning
confidence: 99%
“…While detrimental neurological effects of metals have been established during development in both children (Sharma and Mogra 2014) and animals (Jones et al 2008), though this is controversial as some studies show no consistent effects (Buchanan et al 2011; Taylor et al 2018). Adult animal models using higher occupational exposures to Pb have been exploited to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…In our parallel paper [1] we show there was no evidence to support a role of prenatal exposure to heavy metals at these levels on motor skills in the child at age 7 years measured using the Movement ABC. Here we show ( Table 1 , Table 2 , Table 3 , Table 4 , Table 5 , Table 6 ): Publications using measures of child motor skills in the ALSPAC cohort.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 63%
“…In this paper, we describe data acquisition of scores from subtests of the Movement ABC at 7 years. We also include data from models of associations with prenatal blood lead, cadmium and mercury concentrations to support the main analyses in our parallel paper [1] .…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation